2022
DOI: 10.1021/acs.jpca.1c10112
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Theoretical Investigation of the Gas-Phase C(3P) + N2O Reaction. Low Temperature Rate Constants and Astrochemical Implications

Abstract: The reaction between atomic carbon in its ground electronic state, C( 3 P), and nitrous oxide, N2O, has been studied below room temperature due to its potential importance for astrochemistry, with both species considered to be present at high abundance levels in a range of interstellar environments. On the experimental side, we measured rate constants for this reaction over the 50-296 K range using a continuous supersonic flow reactor. C( 3 P) atoms were generated by the pulsed photolysis of carbon tetrabromid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 70 publications
(113 reference statements)
0
13
0
Order By: Relevance
“…Over the past few years, we have begun to address this issue by examining the reactivity of C( 3 P) with important COMs such as CH 3 OH 14 and CH 3 CN 15 and other molecules that are thought to be formed primarily on interstellar ices such as N 2 O. 5 At the present time, the chemical processes leading to the formation of many of the observed interstellar COMs are not well constrained in a general sense. Among them, acetone, Sgr B2 (OH) by Combes et al 16 in 1987 with a derived column density of 5 × 10 13 cm −2 corresponding to a relative abundance (with respect to H 2 ) of 5 × 10 −11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, we have begun to address this issue by examining the reactivity of C( 3 P) with important COMs such as CH 3 OH 14 and CH 3 CN 15 and other molecules that are thought to be formed primarily on interstellar ices such as N 2 O. 5 At the present time, the chemical processes leading to the formation of many of the observed interstellar COMs are not well constrained in a general sense. Among them, acetone, Sgr B2 (OH) by Combes et al 16 in 1987 with a derived column density of 5 × 10 13 cm −2 corresponding to a relative abundance (with respect to H 2 ) of 5 × 10 −11 .…”
Section: Introductionmentioning
confidence: 99%
“…Although there are numerous studies of the kinetics and dynamics , of C( 3 P) reactions with a wide range of unsaturated hydrocarbons, there are relatively few studies of its reactions with organic molecules containing other types of functional groups such as those found in complex organic molecules (COMs). Over the past few years, we have begun to address this issue by examining the reactivity of C( 3 P) with important COMs such as CH 3 OH and CH 3 CN and other molecules that are thought to be formed primarily on interstellar ices such as N 2 O …”
Section: Introductionmentioning
confidence: 99%
“…The principal attributes of this system have been presented in earlier work, 62 while the main modifications that have been made to allow us to follow the kinetics of atomic radical reactions are described in later work. 63–66 Three different Laval nozzles based on the carrier gases Ar or N 2 were employed during this investigation to access four different low temperature flows between 50 and 177 K (one nozzle was used with both Ar and N 2 to generate flows with characteristic temperatures of 127 and 177 K, respectively). The nozzle properties are summarized in Table 1 of Nuñez-Reyes et al 43 Room temperature measurements (296 K) were conducted with Ar as the carrier gas in the absence of a Laval nozzle and by reducing the flow velocity to avoid pressure gradients in the reactor.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The principal attributes of this system have been presented in earlier work, 62 while the main modifications that have been made to allow us to follow the kinetics of atomic radical reactions are described in later work. [63][64][65][66]…”
Section: Kinetic Experimentsmentioning
confidence: 99%
“…20 However, this is hardly the only novel result. In this virtual special issue, N 2 O is reacted with C( 3 P), producing rate coefficients for such chemical processes, 21 and a similar study on fluoromethane and calcium atomic cations is also reported. 22 Additionally, the deuterated ethynyl radical is reacted with propylene producing a wealth of hydrocarbons, 23 NO + the propargyl radical generates branching ratios for eight common astrochemical products, 24 furan + H 2 reactions generate various c-C 4 H x O (x = 4−8) species, 25 myriad nitrous oxides are synthesized in H 2 O−N 2 O/N 2 ice mixtures, 26,27 dinitriles are shown to be produced from gas-phase reactions of cyano radicals and cyanoethane, 28 and porous amorphous solid water appears to catalyze interstellar organic chemistry.…”
mentioning
confidence: 89%